Relationship between Maternal Blood Vitamin D Levels and Pregnancy Outcomes: A Review Article - Maryam Rostami; Fahimeh Ramezani Tehrani; Masoomeh Simbar; Farhad Hossein Panah (Fasa University of Medical Sciences, 2016)
Background & Objective: Vitamin D deficiency is common during pregnancy and at delivery. Recent data suggest that vitamin D deficiency in mothers is associated with some adverse pregnancy outcomes. This study is designed to determine the relationship between the low maternal serum vitamin D levels and several pregnancy outcomes such as: pre-eclampsia, gestational diabetes, bacterial vaginosis and caesarean section. Material & Methods: This study is a review of the observational study (descriptive and analytic) articles published during 10 years (2000-2014) in English with full text which were indexed in PubMed, Scopus, Google Scholar, Iranmedex, Science Direct and and the SID databases. Results: A collection of 25 observational study from 168 articles which were related to 25-hydroxyvitamin D and adverse pregnancy outcomes were studied. The results indicated that the low levels of serum 25(OH)D in pregnant women is a risk factor for pre-eclampsia, bacterial vaginosis and cesarean section, but in relation to preeclapsia this indication is focuse on the second and the third trimester of pregnancy and there is no agreement about the risk for gestational diabetes and vitamin D deficiency among all the researches. Conclusion: Several pregnancy outcomes may be related to mothers' serum 25(OH)D levels. However there is a significant need to perform more researches such as randomized clinical trials to investigate the effect of supplementation and screening on the maternal and neonatal outcomes.